PEMBANGUNAN SEBAGAI MODERNISASI: PANDANGAN KRITIS TERHADAP PEMBANGUNAN INFRASTRUKTUR DI INDONESIA - Rahayu, Febri Puja (Triwikrama: Jurnal Ilmu Sosial, 2025)
Abstract Infrastructure development in Indonesia is an indicator of a country's progress. However, in its implementation there are various obstacles and challenges faced by the government and society. This article will discuss a critical view of infrastructure development in Indonesia as a modernization effort. Infrastructure development in Indonesia faces problems in social, economic and environmental aspects. Various policies and strategies need to be adopted to optimize infrastructure development in the context of modernization efforts. Keywords: three to five words or phrases that it’s important, specific, and representative for the article. Abstrak Pembangunan infrastruktur di Indonesia merupakan salah satu indikator kemajuan suatu negara. Namun, dalam pelaksanaannya terdapat berbagai kendala dan tantangan yang dihadapi oleh pemerintah maupun masyarakat. Artikel ini akan membahas tentang pandangan kritis terhadap pembangunan infrastruktur di Indonesia sebagai upaya modernisasi. Pembangunan infrastruktur di Indonesia menghadapi masalah dalam aspek sosial, ekonomi, dan lingkungan. Berbagai kebijakan dan strategi perlu diadopsi untuk mengoptimalkan pembangunan infrastruktur dalam rangka upaya modernisasi. Kata kunci: Pembangunan, Infrastruktur, Modernisasi, Keberlanjutan.